Smart rice cooker - Mohammed Salleh, Nur Anis Nabilah (2022)
Singer is a well-known global brand for its sewing machines. Singer has opened its own branches all over the world as a result of its worldwide popularity. The Singer brand has been trusted for centuries for its sewing machines for both household and industrial usage. The same spirit of practical design and creative invention that defined the company in the beginning push Singer to continue producing quality products. These days, the company has just introduced a range of household appliances, including small kitchen machines that can help people live better lives. In this case study, the focus will be on the kitchen appliances, namely the Singer rice cooker to analyse, research and identify the present difficulties with the goods as well as to suggest a viable solution that the company may apply to enhance the existing products. In Malaysia, Singer has approximately 460 retail locations in major cities, suburbs and rural areas. With the quality and budget-friendly machines, Singer has durable and long-lasting products. This helps Singer to keep its reputation as a trustworthy brand although there are several competitors in the same field such as Khind, Panasonic, Ogawa and others. Hence, the general information of the company and the SWOT analysis of Singer’s rice cooker is explored to understand the company better as well as to analyse the major problem of the rice cooker. The general information of the company includes the background information, the organizational structure, the company’s products and its technology as well as its business, marketing and operational strategy. While the SWOT analysis of Singer’s rice cooker contains the product strength, weakness, opportunities and risks then based on this analysis, a new solution for the rice cooker is recommended in the later sub-topic. The solution is made to help the company to overcome the crisis and to improve their product’s technology.